The precious content of the olive mill wastewater: the protective effect of the antioxidant fraction in cell cultures. Issue 1 (1st January 2018) - Giacomazza, Daniela; D'Andrea, Daniela; Provenzano, Alessia; Picone, Pasquale; Provenzano, Fiorenza; Guarrasi, Valeria; Raimondo, Marco; San Biagio, Pier Luigi; Passantino, Rosa; Mangione, Maria Rosalia; Di Carlo, Marta; Costa, Maria Assunta
ABSTRACT: Oxidative stress and mitochondrial dysfunction play an important role in the onset of neurodegenerative diseases; thus, the antioxidant use could be a promising preventive or therapeutic intervention. The food and agricultural industries generate huge quantities of by-products rich in biophenolic compounds. If, on the one hand, they represent a serious environmental problem, on the other hand, are valuable natural sources of antioxidants. In the present work, the total phenolic content and the antioxidant power of the wastewater derived from the production of four Sicilian extra virgin olive oils are shown. Four biophenols, hydroxytyrosol and tyrosol alcohols and caffeic acid (CA) and p -coumaric acids, were identified and quantified and their antioxidant ability determined. Their effects in counteracting Abeta1-42 oligomer oxidative damage in LAN5 cell culture were investigated. Results indicated that CA was the most effective compound in counteracting the cell damages induced by Abeta1-42 oligomers.